Diurnal foraging of a wild coral‐reef fish Parapercis australis in relation to late‐summer temperatures. Issue 1 (30th August 2018) - Chase, Tory John; Nowicki, Jessica P.; Coker, Darren J.
Abstract : In situ observations of diurnal foraging behaviour of a common site‐attached shallow reef mesopredator Parapercis australis during late summer, revealed that although diet composition was unaffected by seawater temperature (range 28.3–32.4°C), feeding strikes and distance moved increased with temperature up to 30.5°C, beyond which they sharply declined, indicative of currently living beyond their thermal optimum. Diel feeding strikes and distance moved were however, tightly linked to ambient temperature as it related to the population's apparent thermal optimum, peaking at times when it was approached (1230 and 1700 h) and declining up to four fold at times deviating from this. These findings suggest that although this population may be currently living beyond its thermal optimum, it copes by down regulating energetically costly foraging movement and consumption and under future oceanic temperatures, these behavioural modifications are probably insufficient to avoid deleterious effects on population viability without the aid of long‐term acclimation or adaptation.